Statistical modelling of the conductivity performance of poly(3,4-ethylene- dioxythiophene/poly(styrene sulfonic acid) films - Diah, A.W.M.; Holdsworth, C.I.; Nur, Darfiana; Beh, E. (BENTHAM SCIENCE PUBL LTD, 2016)
This paper presents a comprehensive statistical evaluation of the conductivity performance of PEDOT/PSS films generated at various spin coating speeds (1000 to 5000 rpm) by correspondence analysis (CA), regression and ANOVA models. Poly(3,4-ethylenedioxythiophene) (PEDOT) is a highly conducting insoluble polymer which, when doped with poly(styrene sulfonic acid) (PSS) in water, results in a dispersion with good film forming properties. Our interest in PEDOT/PSS is in its application as an interfacial layer and gate electrode in organic photovoltaic and organic field effect transistor devices, respectively. The generation of a homogeneous spun-cast layer of PEDOT/PSS over the entire substrate for these intended applications is a function of the spin-coating speed which, in turn, affects the thickness of the film and, consequently, its conductivity measured by the four point probe. From correspondence analysis, we find that only the 1000 rpm spin-coating speed is strongly associated with high thickness and high resistivity (i.e. low conductivity), although further analysis of speeds 2000 - 5000 rpm shows that the spin-coating speed is still associated with the thickness of the films, and subsequently, their conductivities, such that the thinnest and most conductive films result from the highest spin-coating speed (5000 rpm). We also observed the phenomenon of the horseshoe effect from the CA displays and discussed the reasons for not resorting to detrending solutions for dealing with its presence. From multiple and nonlinear regression models, spin-coating speeds 1000 and 2000 rpm were found to produce films of less precise conductivity values as reflected in the absolute value of mean of residuals of nonlinear regression models while more precise and optimal conductivity values are obtained when the films are generated between 3000 and 5000 rpm. The ANOVA models showed that the means of conductivity of films obtained at 1000 rpm is statistically significantly different to those from higher spin coating speeds and that there is no significant difference between the conductivity of films generated using spin coating speeds 2000 and 3000 rpm and between spin coating speeds 4000 and 5000 rpm. Further, the conductivity of films from spin coating speeds 4000-5000 rpm are higher and more precise than those obtained at 2000-3000 rpm. Based on the results of this study, we have standardised conductivity measurements of PEDOT/PSS films using the four-point probe by spin-coating at 4000-5000 rpm in order to obtain optimal and reproducible conductivity values.